2014
DOI: 10.1371/journal.pone.0089395
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Two-Color Real-Time PCR Method for Quality-Controlled Molecular Diagnostic Testing of FFPE Samples

Abstract: BackgroundReverse transcription quantitative real-time PCR (RT-qPCR) tests support personalized cancer treatment through more clinically meaningful diagnosis. However, samples obtained through standard clinical pathology procedures are formalin-fixed, paraffin-embedded (FFPE) and yield small samples with low integrity RNA containing PCR interfering substances. RT-qPCR tests able to assess FFPE samples with quality control and inter-laboratory reproducibility are needed.MethodsWe developed an RT-qPCR method by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…An advantage of FFPE samples is that they can be easily archived and that many cohorts have long time follow-up clinical data available, which greatly facilitates clinical studies. Even though the extracted RNA from FFPE samples may be of relatively low quality, multiple recent studies have shown promising results when utilizing degraded RNA extracted from archival FFPE samples for quantifying gene expression levels by optimized qRT-PCR methods [5] [7] . One example is the Prostatype qRT-PCR kit, which is developed and optimized for measuring the gene expression levels of a gene signature of IGFBP3, F3 and VGLL3 particularly in FFPE samples.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of FFPE samples is that they can be easily archived and that many cohorts have long time follow-up clinical data available, which greatly facilitates clinical studies. Even though the extracted RNA from FFPE samples may be of relatively low quality, multiple recent studies have shown promising results when utilizing degraded RNA extracted from archival FFPE samples for quantifying gene expression levels by optimized qRT-PCR methods [5] [7] . One example is the Prostatype qRT-PCR kit, which is developed and optimized for measuring the gene expression levels of a gene signature of IGFBP3, F3 and VGLL3 particularly in FFPE samples.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the probe length limitation, RT-MLPA can only detect up to 45 targets [ 12 ] or 90-100 host genes in a single reaction using dual-color assay (dcRT-MLPA) [ 14 ]. To improve the throughput and simplify the operating process, we applied Next-Generation Sequencing (NGS) technology to replace the capillary electrophoresis in RT-MLPA method.…”
Section: Resultsmentioning
confidence: 99%
“…After PCR with P5/P7 adaptor primers RT-MLPSeq Libraries from FFPE RNA were successfully prepared ( Supplementary Figure 2 ) and sequenced. Meanwhile we applied RT-qPCR methods to measure RNA expression as previous reported [ 14 ] and compared with results derived from RT-MLPSeq for the same sample. The mRNA expression levels of 16 cancer-associated genes (Ki67, STK15, Survivin, CCNB1, MYBL2, GRB7, HER2, MMP11, CTSL2, ER, PGR, BCL2, SCUBE2, GSTM1, CD68, BAG1) detected by both methods were normalized to 5 reference genes (ACTB, GAPDH, RPLPO, GUSB, TFRC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations